Improving Pediatric Care for Epileptic Children - What Does the Pediatrician Needs to Know about Antiepileptic Drugs? - Khaled Saad (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2015)
While sharing a common property of suppressing seizures, anti epileptic drugs (AEDs) have many different pharmacological profiles that are relevant when selecting and prescribing these agents in children with epilepsy and other conditions. This includes pharmacokinetic properties, drug-drug interactions, and side effect profiles and toxicities [1]. Over the past two decades, the number of AEDs has more than doubled. Unlike some of the former AEDs such as phenobarbital and phenytoin, many of the currently AEDs have simple pharmacokinetics and less side effects on liver. This explains into a generally lower rate of side effects, reduced need for serum monitoring, once or twice daily dosing and fewer drug-drug interactions. Despite these advantages, however, there are few data to suggest significant differences in effectiveness among the older AEDs [1,2].